Debe reformarse la Ley y Reglamento del Sistema Nacional de Contratación Pública, incluyendo una norma que permita establecer la forma en que se determina el presupuesto referencial en la fase precontractual - Soria Pugo, María Gabriela (2015)
The topic that I decided to develop called "must reform LAW AND REGULATION OF THE NATIONAL procurement, including a rule allowing ESTABLISH HOW determine the budget pre-contractual stage referential", so I would make the summary thereof. One of the main problems facing the National Public Procurement System is the determination of the reference budget, a server (a) that calculates "erroneously" referential budget either through ignorance or in order to benefit, not only causing a prejudice to the State, but additionally creates uncertainty for other entities acting in good faith, as they leave a record in the procurement portal of the acquisition of goods or rendering of a service overrated, it can be taken as a reference for other processes, it is a serious distortion in the market. The fundamental problem is the discretion of the contracting entity to set a benchmark in its own budget and convenience studies that made server, this could regulate the extent that an independent body (which may be the SERCOP as the governing body System) engage in conduct technical studies and updated of goods and services demanded by the State, it is made available to the contracting entities for mandatory prior to the start of a recruitment process